2014
DOI: 10.1002/mc.22250
|View full text |Cite
|
Sign up to set email alerts
|

Rectal cancer profiling identifies distinct subtypes in India based on age at onset, genetic, epigenetic and clinicopathological characteristics

Abstract: Rectal cancer is a heterogeneous disease that develops through multiple pathways characterized by genetic and epigenetic alterations. India has a comparatively higher proportion of rectal cancers and early-onset cases. We analyzed genetic (KRAS, TP53 and BRAF mutations, and MSI), epigenetic alterations (CpG island methylation detection of 10 tumor-related genes/loci), the associated clinicopathological features and survival trend in 80 primary rectal cancer patients from India. MSI was detected using BAT 25 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Moreover, little is known about the molecular alterations aiding the malignant transformation in UC patients in Indian population. Recently, few reports have highlighted close association of molecular signature patterns identified in CRC in India and that of the western population (Gupta et al , 2010; Laskar et al , 2015). In colorectal carcinoma, the malignant transformation occurs by acquiring series of driver mutations in sequential manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, little is known about the molecular alterations aiding the malignant transformation in UC patients in Indian population. Recently, few reports have highlighted close association of molecular signature patterns identified in CRC in India and that of the western population (Gupta et al , 2010; Laskar et al , 2015). In colorectal carcinoma, the malignant transformation occurs by acquiring series of driver mutations in sequential manner.…”
Section: Discussionmentioning
confidence: 99%
“…At present, little is known about the molecular alterations that govern the colitis-derived neoplasia in several population. UC-associated CRC studies have shown sequential mutations in the KRAS, BRAF and TP53 genes in an Indian population (Shivakumar et al , 2012; Laskar et al , 2015). Previously, our group has reported few molecular signatures using conventional Sanger sequencing, PCR-RFLP and multiplex PCR (Shivakumar et al , 2012).…”
mentioning
confidence: 99%
“…With several decades of CRC molecular biology research and more than a decade of studies involving targeted and whole exome/genome sequencing, one would expect to have identified all important CRC genes. Nevertheless, by exclusively targeting tumors that a) originated in the rectum, b) were from patients aged 60 years or lower (EOSRC, hugely under-represented in most CRC genomic studies) and c) were from a population shown previously to exhibit deviations from the canonical CRC dogma 28, 29, 42 , we increased the likelihood of identifying a hitherto poorly studied albeit important CRC gene.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter hypermethylation profile of tumor-related genes was anticipated to be crucial and frequent in different cancers. Many epigenetic events in carcinogenic pathways have been studied recently and revealed the methods for detecting CpG island promoter methylation pattern to stratify high risk groups among different cancers [ 15 , 17 , 18 , 34 ]. This helps in detection of early onset of cancer, and predicts clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Promoter methylation status of tumor-related genes ( RASSF1 , DAPK , ECAD , BRCA1 , MLH1 , p16 and GSTP1 ) and three methylated loci ( MINT1 , MINT2 , and MINT31 ) were analyzed using Methylation Specific PCR (MSP) primers ( S2 Table ). For MSP assay, DNA samples were subjected to modification using Imprint1 DNA Modification kit (Sigma–Aldrich, St. Louis, MO), following instructions as described by manufacturer’s [ 18 ]. In this procedure, DNA denaturation and bisulfite modification are carried out simultaneously.…”
Section: Methodsmentioning
confidence: 99%